2018
DOI: 10.1590/1678-5150-pvb-5195
|View full text |Cite
|
Sign up to set email alerts
|

Graduação histológica e aspectos clínico-patológicos relacionados em 22 meningiomas de cães

Abstract: Intracranial and supratentorial meningiomas were the most frequent in relation to the other intracranial or intraspinal sites. The intracranial ones were characterized mainly by clinical signs of thalamic-cortical alteration. Intraspinal ones were mainly characterized by ataxia. G-I meningiomas were the most frequent (63.6%) in dogs, followed by G-III (22.7%) and G-II (13.6%). GI were characterized by having the psammomatous subtype as the most frequent, more than one morphological pattern in the same tumor, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…CN invasion and, occasionally, compression were identified in VR group dogs with pneumonia, commonly presenting with related clinical signs. A retrospective study showed that CNs V, VII, IX, X, and XII dysfunction was observed in 16.7% of dogs with intracranial meningioma (Areco et al 2018). CN dysfunction was the most common clinical sign after convulsive crisis, absent thalamocortical reactions, altered consciousness or behavior, and circling behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CN invasion and, occasionally, compression were identified in VR group dogs with pneumonia, commonly presenting with related clinical signs. A retrospective study showed that CNs V, VII, IX, X, and XII dysfunction was observed in 16.7% of dogs with intracranial meningioma (Areco et al 2018). CN dysfunction was the most common clinical sign after convulsive crisis, absent thalamocortical reactions, altered consciousness or behavior, and circling behavior.…”
Section: Discussionmentioning
confidence: 99%
“…It may present with an altered state of consciousness, seizures, and vestibular dysfunction (Motta et al 2012). Like many other neurological deficits, the clinical signs commonly reflect neuroanatomical tumor distribution (Areco et al 2018). A suitable example would be neurogenic swallowing disorders following cranial nerve (CN) deficits due to posterior fossa or skull base tumors (McCulloch & Jaffe 2006, Finsterer & Grisold 2015, Kumar et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Nos meningiomas meningoteliais as células simulam um sincício formando lóbulos de tamanhos variados delimitados por finos feixes de colágeno. Nos casos de meningiomas psamomatosos se observa a presença de ninhos celulares com presença de corpúsculos calcificados (corpos psamomatosos) (ARECO et al, 2018). Os astrocitomas difusos de alto grau são densamente celulares com células que variam de ovoides a poligonais e apresentam alta atividade mitótica.…”
Section: Discussionunclassified
“…Assim como visto nesse trabalho, um estudo com 173 casos de pacientes com tumores intracranianos descreve o meningioma como o tumor mais comum acometendo 45% dos casos . Apesar do número reduzido de casos observou-se uma porcentagem maior de meningiomas conforme descrito em diversos estudos (JOSÉ-LOPEZ et al, 2021;MILLER et al, 2019;ARECO et al 2018;. Os subtipos de meningiomas mais encontrados são o meningotelial e o transicional, segundo STURGES et al (2008), conforme encontrado nesse estudo.…”
Section: Discussionunclassified
See 1 more Smart Citation